Efecto de la fertilización edáfica y foliar en híbridos de maíz (Zea mays L.), en la zona de Puebloviejo - Cevallos Barros, Haydee Idolina (2019)
VIII. SUMMARY The present experimental work was carried out in the lands of Mrs. Idolina Barros Torres, in the "El Salto" farm; located in the Puebloviejo Canton, whose coordinates are 110597.97 UTM of South Latitude and 277438.26 UTM of West Longitude, at an altitude of 7 masl. The area is characterized by having an average temperature of 25.5 ° C, relative humidity of 78.7% and annual precipitation of 2100 mm. The soil is flat topography, loam-silty texture and regular drainage. Seeds of Supreme and Thunder hybrid maize were used as planting material, complemented with treatments of soil fertilizers combined with organic biostimulants such as 120 kg / ha of N + 60 kg of P2O5 + 80 Kg of K2O + Eco-hormone 0.5 L / ha; 60 Kg / ha of N + 30 kg of P2O5 + 40 Kg of K2O + EcoHormone 0.5 L / ha and Witness (According to the results of the soil analysis). The Experimental Design of "Random Complete Blocks" was used in factorial arrangement A x B, where Factor A was maize hybrids, Factor B edaphic fertilizers combined with organic biostimulants and four repetitions. The comparison of treatment averages was performed with the Tukey test at 0.95 of significance. For the execution of the trial, all the agricultural practices and work that the crop requires for its normal development were carried out, such as soil analysis, land preparation, sowing, weed control, phytosanitary control, fertilization, irrigation and harvesting. Based on the results obtained, it was determined that edaphic and foliar fertilization had positive effects on maize hybrids (Zea mays L.) in the Puebloviejo area; the agronomic characteristics such as plant height, cob insertion height, cob diameter and length, grains per ear, weight of 1000 grains and grain-to-grain ratio reported better results in the Thunder hybrid applying 120 kg / ha of N + 60 kg of P2O5 + 80 Kg of K2O + Ecohormone 0.5 L / ha and the highest grain yield and economic analysis was achieved by the Thunder hybrid with 120 Kg / ha of N + 60 kg of P2O5 + 80 Kg of K2O + Ecohormone 0, 5 L / ha with 6884.2 kg / ha.